Incidence and risk factors of retinopathy of prematurity in Western India – Report from A Regional Institute of Ophthalmology - Vasavada, Dhaivat; Sengupta, Sabyasachi; Prajapati, Vipul K; Patel, Shashank (Nepalese Journal of Ophthalmology, 2018)
Introduction: Retinopathy of prematurity is an important cause of childhood blindness amongst premature babies in developing as well as developed world. Objectives: To report the incidence and risk factors of ROP from a regional institute of Ophthalmology in western India and compare it with the existing scenario. Materials and Methods: This was prospective observational study of babies born at <34 weeks of gestational and/or <1700 grams birth weight between January 2012 and October 2013. Birth related information viz. O2 administration was recorded in consultation with a neonatologist and babies were evaluated for the presence of ROP. Multivariable logistic regression was used to identify risk factors for any-ROP and severe-ROP requiring treatment. Results: Out of 280 babies screened, any-ROP was seen 54 babies(19.28%) out of which, severe-ROP was found in 28 babies(10.29%).Likelihood of developing any-ROP increased 3 fold (95%CI=1.1 – 6.5), and severe-ROP by 7 fold (95%CI=1.6 – 27.5), if oxygen therapy as administered. Older gestational age was associated with reduced likelihood of developing severe-ROP (Odds ratio=0.79, 95%CI=0.6 – 0.9) but not any-ROP. Twenty four babies (86%) with severe ROP responded well to laser or Bevacizumab therapy while 4 babies developed retinal detachment. Conclusion: This is the first report quoting only incidence and risk factors of ROP from western India. One in 5 babies develop any-ROP similar to that reported across rest of the country. The incidence of severe-ROP requiring treatment appears to be marginally higher, and treatment outcomes in these eyes are similar to that reported in literature.